2015
DOI: 10.1002/cjoc.201500697
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Allylic Amination of Morita‐Baylis‐Hillman Acetates Catalyzed by Chiral Thiourea‐Phosphine

Abstract: The enantioselective allylic amination of Morita‐Baylis‐Hillman acetates catalyzed by chiral cyclohexane‐based thiourea‐phosphine catalysts was investigated. In the presence of 20 mol% rosin‐derived thiourea‐phosphine 3j, the chiral amines were obtained in up to 88% yield and up to 85% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In 2015, Wu, Sha, and co-workers synthesized and applied the chiral thiourea-phosphine P87 to the allylic amination of MBH acetates with phthalimide 593 but obtained only moderate to good enantioselectivities (Scheme 525).…”
Section: Nucleophilic Phosphine Catalysis Of Mbh-alcohol Derivatives mentioning
confidence: 99%
“…In 2015, Wu, Sha, and co-workers synthesized and applied the chiral thiourea-phosphine P87 to the allylic amination of MBH acetates with phthalimide 593 but obtained only moderate to good enantioselectivities (Scheme 525).…”
Section: Nucleophilic Phosphine Catalysis Of Mbh-alcohol Derivatives mentioning
confidence: 99%
“…Moreover, rosin-derived thioureas can be used as enantioselective catalysts for many reactions [12]. In recent years these were: Michael addition [223,224], tandem Michael/cyclization sequence [225], asymmetric Michael/hemiketalization [226], asymmetric aza-Henry reaction [227], asymmetric tandem reaction [228], Mannich reaction [229,230], Friedel–Crafts alkylation [231], enantio- and diastereoselective asymmetric addition [232], as well as synthesis of chiral amines [233] or N -protected β-amino malonates [234]. In recent studies rosin-derived thioureas are dominant majority of all investigated rosin-derived catalysts.…”
Section: Rosin-based Chemicalsmentioning
confidence: 99%
“…In 2015, Sha and co‐workers found that the chiral cyclohexane‐based thiourea–phosphine 55 , derived from dehydroabietic acid, was able to catalyze the enantioselective allylic amination of phthalimide with MBH acetates (Scheme a) . Catalyst screening demonstrated that the matching effects between the cyclohexyl backbone and dehydroabietic unit were crucial to achieve a good level of enantioselectivity.…”
Section: Terpene‐derived Organocatalystsmentioning
confidence: 99%
“…In 2015, Sha and co-workers found that the chiral cyclohexane-based thiourea-phosphine 55,d erived from dehydroabietic acid, was able to catalyzet he enantioselectivea llylic amination of phthalimide with MBHa cetates (Scheme 37 a). [110] Cata-Scheme34. Asymmetric Michaela ddition for the synthesis of substituted succinimides promoted by an isosteviol-derived bifunctional thiourea organocatalyst.…”
Section: Rosin-derived Organocatalystsmentioning
confidence: 99%
See 1 more Smart Citation